A comparative study of the oral language in children with normal hearing and children with uni or bilateral hearing loss - Sánchez-Rosso, Ángel Luis; Santiago-Pardo, Rosa Belén; Martínez-Gómez, Beatriz; González-Cano, Anabel; Benito-Orejas, José Ignacio; Muñoz-Moreno, Mª Fe (Revista de Investigación en Logopedia, 2024)
The aim of this study is to compare the development of language and auditory discrimination in a group of children aged 3 to 15 years diagnosed and treated early for congenital hearing loss, uni or bilateral of any defree (mild to profound), to a group of normal hearing children. A total of 143 children were evaluated (57 with bilateral hearing loss, 20 unilateral and 66 with normal hearing). Auditory discrimination was studied using the EDAF test, and language was analysed using the PLON-R test in children from 3 to 6 years of age and the BLOC-SR battery for children of 6 years of age onwards. To find out the social-cultural characteristics of the family group, parents filled in a questionnaire. Considering all the degrees of hearing loss together, in the range of 3 to 6 years of age, there is a delay in linguistic competence in relation to the normal hearing group, which is greater in bilateral hearing loss (1.6 SD) than in unilateral hearing loss (0.9 SD). This gap narrows in the 7-10 year-old period and practically disappears in the 11-15 year-old period. Morphosyntax is the area of language with the greatest impairment. Phonological discrimination of words and auditory sequential memory are closely related to the development of spoken language. In congenital hearing loss, overall language development is delayed in the period from ages 3 to 6 and improving with age up to 15 years old. Individual differences are maintained, which depend not only on the hearing loss, but also on audiological, speech therapy and educational intervention. Morphosyntax is the most vulnerable aspect.
Keywords: Child; Bilateral and unilateral hearing loss; Language outcomes; Speech; Early detection and intervention